A positive electrode material, a lithium-ion battery positive electrode sheet, a method for preparing the lithium-ion battery positive electrode sheet, and a lithium-ion battery.
By splicing nickel-rich oxide with conductive carbon materials with amphiphilic surfactant, combined with specific conductive carbon materials, the problems of poor conductivity and low stability of high-nickel positive electrode materials in lithium-ion batteries are solved, and low cost and high Energy density lithium-ion battery positive electrode sheet.
Patent Information
- Application Number
- CN202111145055.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-09-28
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2041-09-28
AI Technical Summary
The use of existing high-nickel positive electrode materials in lithium-ion batteries has problems such as poor conductivity, low stability and poor processing performance, resulting in high energy density and production costs.
Using amphiphilic surfactant to splice and match nickel-rich oxides with conductive carbon materials, reduce the amount of conductive carbon materials and binders, increase the proportion of active substances, and improve the processing of materials through specific conductive carbon materials matching and processing methods. performance.
The lithium-ion battery positive electrode sheet with low processing costs and ultra-high active substances has been achieved, which improves the battery's energy density and processing performance and reduces production costs.
Smart Images

Figure BDA0003285153540000111 
Figure BDA0003285153540000121 
Figure BDA0003285153540000131
Abstract
Description
Technical Field
[0001] The present application relates to the field of batteries, and in particular to a positive electrode material, a positive electrode sheet for a lithium-ion battery, a method for preparing the positive electrode sheet for a lithium-ion battery, and a lithium-ion battery. Background Art
[0002] A key factor restricting the development of new energy vehicles is the cruising range of electric vehicles, and it is crucial to improve the energy density of power batteries. High-nickel positive electrode materials have great advantages in energy density, but the use of high-nickel materials in power lithium-ion batteries still faces some problems. First, high-nickel materials have poor conductivity, and additional materials need to be added as conductive carbon materials. At the same time, additional binders need to be added to ensure the stability of the electrode, so that the proportion of active materials in the positive electrode of lithium-ion batteries is low, affecting the energy density; second, the higher the nickel content, although it can provide higher capacity, but the worse the stability, the more challenges will be faced in material processing, such as ultra-high nickel positive electrode materials are easy to gel when formulated into slurry, and have higher environmental requirements. Therefore, it is very important to rationally design the combination of high-nickel positive electrode materials, conductive carbon materials and binders, increase the proportion of positive electrode active materials, ensure energy density, and improve the processing performance of materials and reduce production costs.
[0003] There are many existing methods for preparing composite positive electrode materials, but most of them have certain defects. For example, at present, the positive electrode of lithium-ion batteries generally adds polymer binders (such as polyvinylidene fluoride) and carbon-based conductive carbon materials with large specific surface area (such as conductive carbon black) during homogenization. Unreasonable selection and matching of conductive carbon materials will lead to poor and uneven conductivity of the pole piece. In order to improve the conductivity of the pole piece, the existing positive electrode formula will use a higher content of conductive carbon materials, resulting in a decrease in the proportion of positive electrode active materials, affecting the battery energy density and also having an adverse effect on processing performance. Alternatively, carbon materials and positive electrode materials are dispersed in water, dried, and then heated and carbonized under a protective atmosphere to obtain carbon-coated positive electrode materials. Due to the need for heating, it will have an adverse effect on the material itself, and the proportion of active materials is low. Another preparation method is that the positive temperature coefficient conductive polymer and carbon-based conductive carbon material are outside the electrode active material matrix. When the electrochemical energy storage device fails, the positive temperature coefficient conductive polymer layer will change from the conductive state to the electronic insulation state, thereby cutting off the electron source of the internal reaction of the electrochemical energy storage device. In terms of preparation methods, the prior art has disclosed that the positive temperature coefficient conductive polymer, carbon-based conductive carbon material, and electrode active material matrix are uniformly dispersed in deionized water and continuously stirred for 1 to 10 hours, and then vacuum spray dried after the stirring is completed. However, when using the positive temperature coefficient conductive polymer, the positive electrode surface deteriorates due to the polymerization process during the collage process. Summary of the invention
[0004] The present application aims to solve at least one of the technical problems existing in the prior art. To this end, one purpose of the present application is to propose a positive electrode material, which reduces the amount of conductive carbon material in the positive electrode material and has a higher proportion of active material.
[0005] Another object of the present application is to provide a lithium-ion battery positive electrode sheet, wherein the lithium-ion battery positive electrode sheet comprises the positive electrode material.
[0006] The third object of the present application is to provide a method for preparing a positive electrode sheet of a lithium-ion battery.
[0007] The fourth objective of the present application is to provide a lithium-ion battery.
[0008] According to the positive electrode material of the first aspect embodiment of the present application, it includes: an amphiphilic surfactant, a binder, a nickel-rich oxide and a conductive carbon material, the nickel-rich oxide and the conductive carbon material are spliced and matched by the amphiphilic surfactant; the mass percentage of the conductive carbon material in the positive electrode material is w1, wherein the w1 satisfies: w1≤2wt%.
[0009] According to the positive electrode material of the specific embodiment of the present application, a method of pasting a conductive carbon material with a high-nickel positive electrode material is proposed, which can not only minimize the amount of conductive carbon material and binder used and increase the proportion of active substances, but also improve the material processing performance, and finally obtain a lithium-ion battery positive electrode sheet with low processing cost and ultra-high active substance proportion.
[0010] According to some embodiments of the present application, D50 of the nickel-rich oxide satisfies: 0.9 μm≤D50≤15 μm.
[0011] According to some embodiments of the present application, D50 of the nickel-rich oxide satisfies: 3.0 μm≤D50≤11 μm.
[0012] According to some embodiments of the present application, the conductive carbon material is selected from one or more of a zero-dimensional conductive carbon material, a one-dimensional conductive carbon material, and a two-dimensional conductive carbon material.
[0013] According to some embodiments of the present application, the conductive carbon material includes a zero-dimensional conductive carbon material, a one-dimensional conductive carbon material and a two-dimensional conductive carbon material.
[0014] According to some embodiments of the present application, the matching relationship between the nickel-rich oxide and the conductive carbon material is related to the D50 of the nickel-rich oxide and the dimension of the conductive carbon material, and α is defined as the ratio of the zero-dimensional conductive carbon material to the surface area of the nickel-rich oxide, and the ratio of the two-dimensional conductive carbon material to the surface area of the nickel-rich oxide satisfies: 1-α;
[0015] When the D50 satisfies: 0.9 μm ≤ D50 ≤ 3.0 μm, the α satisfies: 0.6 ≤ α ≤ 1.0;
[0016] When the D50 satisfies: 3.0 μm<D50≤11 μm, the α satisfies: 0.3≤α≤0.7;
[0017] When the D50 satisfies: when 11 μm<D50≤15 μm, the α satisfies: 0≤α≤0.4;
[0018] Define t as the aspect ratio of the one-dimensional conductive carbon material;
[0019] When the D50 satisfies: 0.9 μm ≤ D50 ≤ 3.0 μm, the t satisfies: t>700;
[0020] When the D50 satisfies: 3.0 μm<D50≤11 μm, the t satisfies: 300≤t≤700;
[0021] When the D50 satisfies: 11 μm<D50≤15 μm, the t satisfies: t≤300.
[0022] According to some embodiments of the present application, based on the amount of the nickel-rich oxide being 100 g, the amount of the zero-dimensional conductive carbon material corresponding to m is: D0 In g, the thickness of the conductive carbon material is defined as δ, the powder compaction density of the high nickel positive electrode material is defined as p, the conductivity of the conductive carbon material is defined as σ, and the m D0 Satisfies the following formula (I):
[0023] m D0 =4*π*(D50 / 2+r) 2 *4 / 3*r*α*2.2 / σ(I);
[0024] Corresponding to the amount of the two-dimensional conductive carbon material m D2 In g, the following formula (III) is satisfied:
[0025] m D2 =4*π*(D50 / 2) 2 *(1-α)*δ*2.2 / σ(III);
[0026] Corresponding to the amount of the one-dimensional conductive carbon material m D1 In g, the m D1 Satisfies the following formula (II):
[0027] m D1 =100 / (p*4 / 3*π*(D50 / 2) 3 )*8*3D50*π*(3D50 / t)*2*2.2 / σ(II).
[0028] According to some embodiments of the present application, when the D50 satisfies: 0.9 μm ≤ D50 ≤ 3.0 μm,
[0029] The m D0 Meet: 0.5g≤m D0 ≤0.8g; m D1 Meet: 0.08g≤m D1 ≤0.3.g; m D2 Satisfy: 0.1≤m D2 ≤0.3g;
[0030] When the D50 satisfies: 3.0 μm<D50≤11 μm,
[0031] The m D0 Satisfy: 0.3 ≤ m D0 ≤0.7g; m D1 Meet: 0.08g≤m D1 ≤0.3.g; m D2 Satisfy: 0.2 ≤ m D2 ≤0.4g;
[0032] When the D50 satisfies: When 11μm<D50≤15μm,
[0033] The m D0 Satisfy: 0.2 ≤ m D1 ≤0.5g; m D1 Satisfy: 0.08 ≤ m D1 ≤0.3g; m D2 Satisfy: 0.3 ≤ m D2 ≤0.5g.
[0034] According to some embodiments of the present application, the zero-dimensional conductive carbon material is selected from one or more of spherical or point-shaped carbon materials;
[0035] The one-dimensional conductive carbon material is selected from one or more linear or chain-shaped carbon materials;
[0036] The two-dimensional conductive carbon material is selected from one or more of flaky or planar carbon materials.
[0037] According to some embodiments of the present application, the zero-dimensional conductive carbon material is selected from one or more of conductive carbon black, fullerene, and carbon quantum dots;
[0038] The one-dimensional conductive carbon material is selected from one or more of carbon nanotubes and carbon nanofibers;
[0039] The two-dimensional conductive carbon material is selected from one or more of graphene and graphyne.
[0040] According to some embodiments of the present application, the nickel-rich oxide is selected from one or more of a lithium nickel cobalt manganese oxygen ternary layered material, a lithium nickel cobalt aluminum oxygen ternary layered material, and a lithium nickel manganese cobalt aluminum oxygen ternary layered material.
[0041] According to some embodiments of the present application, the lithium nickel cobalt manganese oxygen ternary layered material has the following structure: Li 1+ m Ni x Co y Mn 1-x-y O2, x≥0.6, 0≤y≤0.4, 0≤m≤0.1; the lithium nickel cobalt aluminum oxygen ternary layered material has the following structure: Li 1+m Ni x Co y Al 1-x-y O2, x≥0.6, 0≤y≤0.4, 0≤m≤0.1; the structure of the lithium nickel manganese cobalt aluminum oxygen ternary layered material is as follows: Li 1+m Ni x Co y Mn z Al1-xy-zO2, x≥0.6, 0≤y≤0.4, 0≤z≤0.4, 0≤m≤0.1.
[0042] According to some embodiments of the present application, the surfactant is selected from DSPE-MPEG, CH3(CH2) 11 SO4Na, [(C 16 H 33 )N(CH3)3]Br and PVP.
[0043] A lithium-ion battery positive electrode sheet according to another embodiment of the present application includes the positive electrode material.
[0044] According to the third aspect of the present application, the method for preparing a positive electrode sheet of a lithium-ion battery comprises the following steps:
[0045] Step 1: adding an amphiphilic surfactant to a dispersion of a conductive carbon material;
[0046] Step 2: After the dispersed system obtained in step 1 is evenly dispersed, nickel-rich oxide is added, stirred, and washed to obtain nickel-rich oxide powder with conductive carbon material collaged thereon; after the collage is completed, the powder is collected;
[0047] Step 3: The nickel-rich oxide with the conductive carbon material obtained in step 2 is mixed with a binder and NMP and evenly coated on the aluminum foil; and the positive electrode sheet of the lithium-ion battery is obtained through drying and rolling.
[0048] According to some embodiments of the present application, the mass percentage of the surfactant added in the conductive carbon material dispersion in the step 1 is w2, wherein w2 satisfies: 0.01wt%≤w2≤0.2wt%.
[0049] According to some embodiments of the present application, w2 is 0.04 wt %.
[0050] The lithium-ion battery according to the fourth embodiment of the present application includes the lithium-ion battery positive electrode sheet or the lithium-ion battery positive electrode sheet prepared by the preparation method.
[0051] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. DETAILED DESCRIPTION
[0052] The embodiments of the present application are described in detail below. The specific embodiments are exemplary. The embodiments of the present application are described in detail below with reference to the specific embodiments.
[0053] The following describes in detail the positive electrode material, the positive electrode sheet of a lithium-ion battery, the method for preparing the positive electrode sheet of a lithium-ion battery, and the lithium-ion battery according to the embodiments of the present application.
[0054] In the first aspect of the present application, the present application proposes a positive electrode material, including: an amphiphilic surfactant, a binder, a nickel-rich oxide and a conductive carbon material, the nickel-rich oxide and the conductive carbon material are spliced and matched by the amphiphilic surfactant; the mass percentage of the conductive carbon material in the positive electrode material is w1, wherein w1 satisfies: w1≤2wt%.
[0055] According to the positive electrode material of the specific embodiment of the present application, an amphiphilic surfactant is used as a collage agent. The hydrophilic end of the amphiphilic surfactant can be hydrogen-bonded with the hydroxyl group on the surface of the nickel-rich oxide, while its hydrophobic end maintains a π-π interaction with the conductive carbon material. As a result, the conductive carbon material can be collaged on the surface of the nickel-rich oxide in a face-to-face manner without the need for heating in the middle, which will not cause adverse effects on the material itself and has lower costs.
[0056] According to some embodiments of the present application, the D50 of the nickel-rich oxide satisfies: 0.9μm≤D50≤15μm, preferably, the D50 of the nickel-rich oxide satisfies: 3.0μm≤D50≤11μm. In this way, the D50 range is selected to be 0.9-15 microns, which can cover different types (single crystal, polycrystalline, blended) of high-nickel positive electrode materials, and has wide universality. Among them, 3.0-11 microns is a more preferred range value. If D50 is too small, the particles are too small, and side reactions such as gas production are serious; if D50 is too large, the particles are too large, and the compaction is too small, which affects the battery energy density. Therefore, D50 that is too large or too small will affect the battery performance.
[0057] According to some specific embodiments of the present application, the conductive carbon material includes zero-dimensional conductive carbon material, one-dimensional conductive carbon material and two-dimensional conductive carbon material. The present application defines the selection and matching rules of different conductive carbon materials for different positive electrode materials, further reducing the amount of conductive carbon material in the electrode to less than 2%, and the proportion of active material is higher.
[0058] According to some embodiments of the present application, the matching mode of the nickel-rich oxide and the conductive carbon material is related to the D50 of the nickel-rich oxide and the dimension of the conductive carbon material, and α is defined as the ratio of the zero-dimensional conductive carbon material to the surface area of the nickel-rich oxide, and the ratio of the two-dimensional conductive carbon material to the surface area of the nickel-rich oxide satisfies: 1-α;
[0059] When D50 satisfies: 0.9μm≤D50≤3.0μm, α satisfies: 0.6≤α≤1.0;
[0060] When D50 satisfies: 3.0μm<D50≤11μm, α satisfies: 0.3≤α≤0.7;
[0061] When D50 satisfies: when 11μm<D50≤15μm, α satisfies: 0≤α≤0.4.
[0062] When D50 satisfies: 0.9μm≤D50≤3.0μm, the particle size of the nickel-rich oxide granular material is small, and a larger proportion of zero-dimensional conductive carbon material is used. The zero-dimensional conductive carbon material plays a point-to-point charge transfer connection role.
[0063] When nickel-rich oxide is in the form of larger particles, under the same dosage, the zero-dimensional conductive carbon material has a worse conductive effect than when nickel-rich oxide is in the form of smaller particles, but has a strong liquid retention ability. The two-dimensional conductive carbon material has good conductivity, but if the dosage is increased on small particles, it will affect the diffusion of lithium ions therein.
[0064] In summary, when the nickel-rich oxide particles are small, that is, 0.9μm≤D50≤3.0μm; the proportion of zero-dimensional conductive carbon material to the surface area of nickel-rich oxide is greater than the proportion of two-dimensional conductive carbon material to the surface area of nickel-rich oxide, that is, the total volume of zero-dimensional conductive carbon material is greater than the total volume of two-dimensional conductive carbon material; when the nickel-rich oxide particles satisfy 3.0μm<D50≤11μm, the proportion of zero-dimensional conductive carbon material to the surface area of nickel-rich oxide is equivalent to the proportion of two-dimensional conductive carbon material to the surface area of nickel-rich oxide, that is, the total volume of zero-dimensional conductive carbon material is equivalent to the total volume of two-dimensional conductive carbon material; when the nickel-rich oxide particles satisfy 11μm<D50≤15μm, the proportion of two-dimensional conductive carbon material to the surface area of nickel-rich oxide is greater than the proportion of zero-dimensional conductive carbon material to the surface area of nickel-rich oxide, that is, the total volume of two-dimensional conductive carbon material is greater than the total volume of zero-dimensional conductive carbon material. Preferably, when the nickel-rich oxide particles satisfy 0.9μm≤D50≤3.0μm, the ratio of the zero-dimensional conductive carbon material and the less two-dimensional conductive carbon material to the surface area of the nickel-rich oxide is 0.7 / 0.3; when the nickel-rich oxide particles satisfy 3.0μm<D50≤11μm, the ratio of the zero-dimensional conductive carbon material and the two-dimensional conductive carbon material to the surface area of the nickel-rich oxide is 0.5 / 0.5; when the nickel-rich oxide particles satisfy 11μm<D50≤15μm, the ratio of the zero-dimensional conductive carbon material and the two-dimensional conductive carbon material to the surface area of the nickel-rich oxide is 0.3 / 0.7.
[0065] Define t as the aspect ratio of the one-dimensional conductive carbon material;
[0066] When D50 satisfies: 0.9μm≤D50≤3.0μm, t satisfies: t>700;
[0067] When D50 satisfies: 3.0μm<D50≤11μm, t satisfies: 300≤t≤700;
[0068] When D50 satisfies: 11μm<D50≤15μm, t satisfies: t≤300.
[0069] The one-dimensional conductive carbon material serves as an electron conduction bridge between particles and has little contact with the surface of the positive electrode particles. Compared with the contact area of the zero-dimensional conductive carbon material and the two-dimensional conductive carbon material, it can be ignored as a tolerance.
[0070] According to some embodiments of the present application, based on the amount of nickel-rich oxide being 100 g, the amount of zero-dimensional conductive carbon material corresponding to m is: D0 In g, the thickness of the conductive carbon material is defined as δ, the powder compaction density of the high nickel positive electrode material is defined as p, and the conductivity of the conductive carbon material is defined as σ, m D0 Satisfies the following formula (I):
[0071] m D0=4*π*(D50 / 2+r) 2 *4 / 3*r*α*2.2 / σ(I);
[0072] Corresponding to the amount of two-dimensional conductive carbon material m D2 In g, the following formula (III) is satisfied:
[0073] m D2 =4*π*(D50 / 2) 2 *(1-α)*δ*2.2 / σ(III);
[0074] Corresponding to the amount of one-dimensional conductive carbon material m D1 In g, m D1 Satisfies the following formula (II):
[0075] m D1 =100 / (p*4 / 3*π*(D50 / 2) 3 )*8*3D50*π*(3D50 / t)*2*2.2 / σ(II).
[0076] This application defines the selection and matching rules of different conductive carbon materials for different positive electrode materials, making the selection of conductive carbon materials more reasonable; in addition, amphiphilic surfactants are used as pasting agents to make the conductive carbon materials more evenly and controllably pasted on the nickel-rich oxide surface, further improving the battery energy density.
[0077] Wherein, σ is the conductivity of the conductive carbon material powder. Define D as the dimension of the conductive carbon material. When a zero-dimensional conductive carbon material is selected, D=0; when a one-dimensional carbon material is selected, D=1; when a two-dimensional conductive carbon material is selected, D=2. When D=0, the particle size of the conductive carbon material is defined as 2r. When D=1, the length of the conductive carbon material is defined as l, and the aspect ratio is t. When D=2, the thickness of the conductive carbon material is defined as δ. The compacted density of the nickel-rich oxide powder is defined as p, and 2.2 is the true density of carbon.
[0078] α can be considered that the surface of the positive electrode particles, that is, the α part of the nickel-rich oxide surface is covered by the zero-dimensional conductive carbon material, plus 1-α covered by the two-dimensional conductive carbon material, the surface of the positive electrode particles is completely covered by the conductive carbon material.
[0079] This application first defines the selection and matching rules of different conductive carbon materials for different positive electrode materials, and selects conductive carbon materials of different types and properties according to the D50 of nickel-rich oxides, while minimizing the amount of conductive carbon materials used, ensuring the effectiveness of long-range and short-range transport inside the pole piece. At the same time, this application proposes a method for pasting nickel-rich oxides with conductive carbon materials, which can avoid the problem of uneven dispersion of conductive carbon materials during the slurrying process, and can also improve the processing performance of positive electrode materials. Finally, for different positive electrode materials, positive electrode sheets with low processing costs and ultra-high active material ratios can be prepared.
[0080] According to some other specific embodiments of the present application, when D50 satisfies: 0.9 μm ≤ D50 ≤ 3.0 μm,
[0081] m D0 Meet: 0.5g≤m D0 ≤0.8g;m D1 Meet: 0.08g≤m D1 ≤0.3.g;m D2 Satisfy: 0.1≤m D2 ≤0.3g;
[0082] When D50 satisfies: 3.0μm<D50≤11μm,
[0083] m D0 Satisfy: 0.3 ≤ m D0 ≤0.7g;m D1 Meet: 0.08g≤m D1 ≤0.3.g;m D2 Satisfy: 0.2 ≤ m D2 ≤0.4g;
[0084] When D50 satisfies: When 11μm<D50≤15μm,
[0085] m D0 Satisfy: 0.2 ≤ m D1 ≤0.5g;m D1 Satisfy: 0.08 ≤ m D1 ≤0.3g; m D2 Satisfy: 0.3 ≤ m D2 ≤0.5g.
[0086] According to the preferred embodiment of the present application, when 0.9μm≤D50≤3.0μm, the material particle size is small, and a zero-dimensional + two-dimensional conductive carbon material with a volume ratio of 0.7+0.3 is used. The zero-dimensional conductive carbon material plays a point-to-point charge transfer connection role. Under the same dosage, the conductive effect of large particles is worse than that of small particles, but the liquid retention capacity is strong; the two-dimensional conductive carbon material has good conductivity, but if the dosage on small particles increases, it will affect the diffusion of lithium ions therein. In summary, when the particle size of the positive electrode material particles is small, more zero-dimensional conductive carbon material and less two-dimensional conductive carbon material are used, that is, according to the volume ratio, the zero-dimensional conductive carbon material + two-dimensional conductive carbon material is 0.7+0.3. When the particle size of the nickel-rich oxide is 0.9μm≤D50≤3.0μm, the volume ratio of the zero-dimensional conductive carbon material and the two-dimensional conductive carbon material is 0.5+0.5. When the nickel-rich oxide particles are large, the volume ratio of the zero-dimensional conductive carbon material and the two-dimensional conductive carbon material is 0.3+0.7.
[0087] The one-dimensional conductive carbon material serves as an electron conduction bridge between particles and has little contact with the surface of the positive electrode particles. Compared with the contact area of the zero-dimensional conductive carbon material and the two-dimensional conductive carbon material, it can be ignored as a tolerance.
[0088] More specifically, the amount of the conductive carbon material used in the present invention is as follows:
[0089] (1) When 0.9μm≤D50≤3.0μm
[0090] The amount of zero-dimensional conductive carbon material is m D0 =4*π*(D50 / 2+r) 2 *4 / 3*r*0.7*2.2 / σ(I), about 0.5-0.8g;
[0091] α can be considered that the surface of the positive electrode particles, that is, the α part of the nickel-rich oxide surface is covered by the zero-dimensional conductive carbon material, plus 1-α covered by the two-dimensional conductive carbon material, the surface of the positive electrode particles is completely covered by the conductive carbon material.
[0092] That is, when the particle size of the nickel-rich oxide particles used as the positive electrode material is small, the zero-dimensional conductive carbon material + two-dimensional conductive carbon material of 0.7+0.3 is the preferred choice in terms of volume ratio. The zero-dimensional conductive carbon material plays a point-to-point charge transfer connection role. Under the same dosage, the conductive effect of large particles is worse than that of small particles, but the liquid retention capacity is strong; the two-dimensional conductive carbon material has good conductivity, but if the dosage is increased on small particles, it will affect the diffusion of lithium ions. In summary, when the particle size of the positive electrode particles is small, more zero-dimensional conductive carbon materials and less two-dimensional conductive carbon materials are used, that is, in terms of volume ratio, the ratio of zero-dimensional conductive carbon materials + two-dimensional conductive carbon materials is 0.7+0.3. (The same below, preferably, that is, in terms of volume ratio, the positive electrode material of the medium particles uses a zero-dimensional conductive carbon material + a two-dimensional conductive carbon material in a ratio of 0.5+0.5, and the positive electrode material of the large particles uses a zero-dimensional conductive carbon material + a two-dimensional conductive carbon material in a ratio of 0.3+0.7).
[0093] The one-dimensional conductive carbon material serves as an electron conduction bridge between particles. The amount used and the less contact with the surface of the positive electrode particles can be ignored as a tolerance compared with the contact area of the zero-dimensional conductive carbon material and the two-dimensional conductive carbon material.
[0094] One-dimensional conductive carbon material dosage m D1 =100 / (p*4 / 3*π*(D50 / 2) 3 )*8*3D50*π*(3D50 / t)*2*2.2 / σ, where the aspect ratio t>700 is about 0.08-0.3.g;
[0095] D50 is the average diameter of the particles, and 3D50 is the D50 of three positive electrode particles. If a one-dimensional linear conductive carbon material can connect and bridge 3-4 particles, then at the current level, the conductive network between adjacent particle groups is more effective. Because two-dimensional conductive carbon materials are prone to agglomeration and curling, a margin of twice the theoretical amount is reserved.
[0096] The amount of two-dimensional conductive carbon material is m D2 =4*π*(D50 / 2) 2 *0.3*δ*2.2 / σ, about 0.1-0.3g.
[0097] (2) When 3.0μm<D50≤11μm
[0098] The amount of zero-dimensional conductive carbon material is m D2 =4*π*(D50 / 2+r) 2 *4 / 3*r*0.5*2.2 / σ, about 0.3-0.7g;
[0099] Required amount of one-dimensional conductive carbon material m D1=100 / (p*4 / 3*π*(D50 / 2) 3 )*8*3D50*π*(3D50 / t)*2*2.2 / σ, where the aspect ratio is 300≤t≤700, which is about 0.08-0.3g;
[0100] The amount of two-dimensional conductive carbon material is m D2 =4*π*(D50 / 2) 2 *0.5*δ*2.2 / σ, about 0.2-0.4g.
[0101] (3) When 11μm<D50≤15μm
[0102] The amount of zero-dimensional conductive carbon material is m D2 =4*π*(D50 / 2+r) 2 *4 / 3*r*0.3*2.2 / σ, about 0.2-0.5g;
[0103] Required amount of one-dimensional conductive carbon material m D1 =100 / (p*4 / 3*π*(D50 / 2) 3 )*8*3D50*π*(3D50 / t)*2*2.2 / σ, where the aspect ratio t≤700, is about 0.08-0.3g;
[0104] The amount of two-dimensional conductive carbon material is m D2 =4*π*(D50 / 2) 2 *0.7*δ*2.2 / σ, about 0.3-0.5g.
[0105] In a specific embodiment of the present invention, the positive electrode particle material is preferably nickel-rich oxide, but is not limited thereto.
[0106] According to the positive electrode material of the specific embodiment of the present application, a method of collage of conductive carbon materials with nickel-rich oxide is proposed, which can not only minimize the amount of conductive carbon materials and binders, increase the proportion of active materials, but also improve the material processing performance, and finally obtain a lithium-ion battery positive electrode sheet with low processing cost and ultra-high active material proportion. Specifically analyzed, the size, aspect ratio and dispersibility of the conductive carbon material are the key factors affecting the percolation threshold in the electrode. In addition, the charge transport inside the electrode includes both long-range transport between active material particles and short-range transport within a single electrode. Accordingly, the present application first defines the selection and matching rules of different conductive carbon materials for different positive electrode materials, and selects conductive carbon materials of different types and properties according to the D50 of nickel-rich oxide, while minimizing the amount of conductive carbon materials, ensuring the effectiveness of long-range transport and short-range transport inside the pole piece. At the same time, the method of collage of conductive carbon materials with nickel-rich oxide in the present application can avoid the problem of uneven dispersion of conductive carbon materials during the slurrying process, and can also improve the processing performance of high-nickel positive electrode materials. Ultimately, for different positive electrode materials, positive electrode sheets with low processing costs and ultra-high active material ratio can be prepared.
[0107] According to some embodiments of the present application, the zero-dimensional conductive carbon material is selected from one or more spherical or point-shaped carbon materials; the one-dimensional conductive carbon material is selected from one or more linear or chain-shaped carbon materials; the two-dimensional conductive carbon material is selected from one or more flaky or planar carbon materials.
[0108] According to some specific embodiments of the present application, the zero-dimensional conductive carbon material is selected from one or more of conductive carbon black, fullerene, and carbon quantum dots; the one-dimensional conductive carbon material is selected from one or more of carbon nanotubes and nanocarbon fibers; and the two-dimensional conductive carbon material is selected from one or more of graphene and graphyne.
[0109] According to other embodiments of the present application, the conductive carbon material includes, but is not limited to, zero-dimensional conductive carbon material, one-dimensional conductive carbon material, two-dimensional conductive carbon material, and other conductive carbon materials.
[0110] According to some specific embodiments of the present application, the nickel-rich oxide includes one or more of a lithium nickel cobalt manganese oxygen ternary layered material, a lithium nickel cobalt aluminum oxygen ternary layered material, and a lithium nickel manganese cobalt aluminum oxygen ternary layered material.
[0111] According to some embodiments of the present application, the lithium nickel cobalt manganese oxygen ternary layered material has the following structure: Li 1+ m Ni x Co y Mn 1-x-y O2, x≥0.6, 0≤y≤0.4, 0≤m≤0.1,; lithium nickel cobalt aluminum oxygen ternary layered material, the structure is as follows, Li 1+m Nix Co y Al 1-x-y O2, x≥0.6, 0≤y≤0.4, 0≤m≤0.1; the structure of lithium nickel manganese cobalt aluminum oxygen ternary layered material is as follows, Li1+mNixCoyMnzAl1-xy-zO2, x≥0.6, 0≤y≤0.4, 0≤z≤0.4, 0≤m≤0.1.
[0112] According to some embodiments of the present application, the surfactant includes DSPE-MPEG, CH3(CH2) 11 SO4Na, [(C 16 H 33 )N(CH3)3]Br and PVP.
[0113] According to another aspect of the present application, the positive electrode sheet of a lithium-ion battery comprises the positive electrode material mentioned above, and has low processing cost and ultra-high active material ratio.
[0114] According to the third aspect of the present application, the method for preparing a positive electrode sheet of a lithium-ion battery comprises the following steps:
[0115] Step 1: adding a surfactant to a dispersion of a conductive carbon material;
[0116] Step 2: After the dispersed system obtained in step 1 is evenly dispersed, nickel-rich oxide is added, stirred, and washed to obtain nickel-rich oxide powder with conductive carbon material collaged thereon; after the collage is completed, the powder is collected;
[0117] Step 3: Mix the nickel-rich oxide with the conductive carbon material obtained in step 2 with a binder and NMP and evenly apply the mixture on the aluminum foil; and obtain a positive electrode sheet for a lithium-ion battery after drying and rolling.
[0118] An amphiphilic surfactant is added to the dispersion of the conductive carbon material, and the amphiphilic surfactant is added in the range of 0.01-0.2wt% relative to the dispersion, wherein 0.04wt% is preferred. After uniform dispersion, nickel-rich oxide is added, and the hydrophilic end of the amphiphilic surfactant can be hydrogen-bonded with the hydroxyl group on the surface of the nickel-rich oxide, while the hydrophobic end of the amphiphilic surfactant maintains a π-π interaction with the conductive carbon material, so that the conductive carbon material can be collaged face to face on the surface of the nickel-rich oxide. The presence of the collage layer can not only play a role in constructing a conductive network, but also inhibit the generation of residual alkali on the surface of the nickel-rich oxide, protect the surface of the positive electrode material, and thus improve the battery processing and long-term performance. Finally, for different positive electrode materials, a positive electrode sheet with low processing cost and ultra-high active material ratio can be prepared.
[0119] According to some embodiments of the present application, the mass percentage of the amphiphilic surfactant added in the dispersion of the conductive carbon material in step one is w2, wherein w2 satisfies: 0.01wt%≤w2≤0.2wt%; preferably, w2 is 0.04wt%.
[0120] The lithium-ion battery according to the fourth embodiment of the present application includes the above-mentioned ion battery positive electrode sheet or the ion battery positive electrode sheet prepared by the above-mentioned preparation method.
[0121] The embodiments of the present application are described in detail below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. In addition, unless otherwise explicitly stated, all reagents used in the following embodiments are commercially available or can be synthesized according to this article or known methods, and the reaction conditions not listed are also easily available to those skilled in the art.
[0122] The lithium-ion battery positive electrode sheet of the present application and its preparation method and application are described below through specific embodiments. Specific embodiments
[0124] The preparation process of the positive electrode sheet of the lithium-ion battery in the embodiment of the present application is as follows: an amphiphilic surfactant is added to the dispersion of the conductive carbon material, and after uniform dispersion, a nickel-rich oxide is added, and after collage is completed, the powder is collected to obtain a nickel-rich oxide collaged with the conductive carbon material. The obtained nickel-rich oxide collaged with the conductive carbon material is mixed with a binder and NMP and uniformly coated on an aluminum foil, and a positive electrode sheet with low processing cost and ultra-high active material ratio is obtained after drying and rolling.
[0125] The following are some examples:
[0126] Example 1
[0127] Conductive carbon black (0.5 g), carbon nanotubes (0.3 g), and graphene (0.2 g) were added to 49 g of DMF and mixed evenly. Then DSPE-MPEG (0.08 g) was added to the mixed dispersion and dispersed evenly. Then 100 g of LiNi with a D50 of 2 μm was added. 0.8 Co 0.1 Mn 0.1 (NCM811), vortex stirred for 5 min, washed, dried and collected the powder. The obtained powder was mixed with binder PVDF5130 (0.5 g) and NMP and evenly coated on aluminum foil, dried and rolled to obtain a positive electrode sheet.
[0128] Example 2: The preparation process is the same as that of Example 1, except that NCM811 with a D50 of 2 μm is replaced by NCM811 with a D50 of 10 μm.
[0129] Example 3: The preparation process is the same as that of Example 1, except that NCM811 with a D50 of 2 μm is replaced by NCM811 with a D50 of 15 μm.
[0130] Comparative Example 1: The preparation process is the same as that of Example 1, except that the amount of conductive carbon black used is 0.
[0131] Comparative Example 2: The preparation process is the same as that of Example 1, except that the amount of carbon nanotubes used is 0.
[0132] Comparative Example 3: The preparation process is the same as that of Example 1, except that the amount of graphene used is 0.
[0133] Comparative Example 4: The preparation process is the same as that of Example 1, except that the amount of carbon nanotubes and graphene used is 0.
[0134] Comparative Example 5: The preparation process is the same as that of Example 1, except that the amount of conductive carbon black and graphene used is 0.
[0135] Comparative Example 6: The preparation process is the same as that of Example 1, except that the amount of conductive carbon black and carbon nanotubes used is 0.
[0136] Comparative Example 7: The preparation process is the same as that of Example 1, except that the amount of conductive carbon black, carbon nanotubes and graphene used is 0.
[0137] Comparative Example 8: The preparation process is the same as that of Example 1, except that the amounts of conductive carbon black, carbon nanotubes and graphene are doubled, namely conductive carbon black (1.0 g), carbon nanotubes (0.6 g) and graphene (0.4 g), respectively.
[0138] Comparative Example 9: The preparation process is the same as that of Example 1, except that the amount of the amphiphilic surfactant DSPE-MPEG used is 0.
[0139] Comparative Example 10: The preparation process is the same as that of Example 1, and the amount of the amphiphilic surfactant DSPE-MPEG used is 4 g.
[0140] Comparative Example 11: The preparation process was the same as in Example 1, and the vortex stirring time was 1 min.
[0141] Comparative Example 12: The preparation process was the same as in Example 1, and the vortex stirring time was 10 min.
[0142] The parameters of Examples 1-3 and Comparative Examples 1-12 in Table 1 are as follows:
[0143]
[0144] Performance Testing
[0145] In order to more fully disclose the lithium ion battery positive electrode sheet provided in the embodiment of the present application, the obtained lithium ion battery positive electrode sheet was subjected to a surface free lithium content test, a longitudinal resistivity test, a mixed material gram capacity and capacity retention rate test, and an infrared absorption test, and the obtained results were analyzed:
[0146] 1. Surface free lithium content test
[0147] The free lithium content on the surface of the obtained powder material was tested by potentiometric titration. The test results are shown in Table 2 below.
[0148] Table 2 Comparison of free lithium content on the surface of the embodiment and the comparative example
[0149] Example Lithium hydroxide (ppm) Lithium carbonate (ppm) Example 1 1548.3 1863.4 Example 2 1531.8 1761.3 Example 3 1354.4 1643.1 Comparative Example 1 1864.8 2357.6 Comparative Example 2 1703.4 2164.7 Comparative Example 3 2015.4 2534.1 Comparative Example 4 2159.7 2642.3 Comparative Example 5 2451.1 2865.8 Comparative Example 6 2318.3 2615.4 Comparative Example 7 2751.5 3007.4 Comparative Example 8 1497.8 1874.1 Comparative Example 9 2537.1 2759.3 Comparative Example 10 1531.8 1903.4 Comparative Example 11 2094.5 2245.0 Comparative Example 12 1588.5 1835.4
[0150] It can be seen from Table 2 that the free lithium content on the surface of the nickel-rich oxide positive electrode sheets with reasonable dosage and excessive conductive carbon material collage (Example 1, Comparative Example 8, Comparative Example 10, Comparative Example 12) is significantly lower than that of the positive electrode sheets without collage (Comparative Example 9) and the positive electrode sheets with insufficient conductive carbon material (Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, Comparative Example 5, Comparative Example 6, Comparative Example 7) and the positive electrode sheets with incomplete collage (Comparative Example 9, Comparative Example 11).
[0151] 2. Longitudinal resistivity test
[0152] The longitudinal resistivity of the obtained positive electrode sheet was tested using a longitudinal resistivity meter, and the test results are shown in Table 3.
[0153] Table 3 Longitudinal resistivity of examples and comparative examples
[0154]
[0155]
[0156] As shown in Table 3, the longitudinal resistivity of the nickel-rich positive electrode sheets (Example 1, Comparative Example 8, Comparative Example 10, Comparative Example 12) with reasonable amount and excessive conductive carbon material collage is significantly lower than that of the positive electrode sheet without collage (Comparative Example 9), the positive electrode sheet with insufficient amount of conductive carbon material (Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, Comparative Example 5, Comparative Example 6, Comparative Example 7), and the positive electrode sheet with incomplete collage (Comparative Example 9, Comparative Example 11). This shows that the collage method of conductive carbon materials helps to reduce the amount of conductive carbon materials used, and the reasonable selection of the amount of conductive carbon materials can build an effective conductive network.
[0157] 3. Test of the gram capacity and capacity retention rate of mixed materials
[0158] The positive electrode sheet and the corresponding graphite negative electrode sheet were assembled into a full battery with a capacity of 2.2Ah. The prepared battery was subjected to capacity and cycle tests to obtain the mixed material gram capacity and capacity retention rate. The test results are shown in Table 4.
[0159] Table 4 Example and comparative example mixed material gram capacity and capacity retention rate
[0160]
[0161]
[0162] It can be seen from Table 4 that the nickel-rich oxide positive electrode sheet (Example 1) with a reasonable amount of conductive carbon material collage has the highest mixed capacity and capacity retention rate after cycling, indicating that the use of the collage method and the reasonable selection of the amount of conductive carbon material play an important role in improving the battery energy density and improving the battery life.
[0163] 4. Infrared absorption test
[0164] The powder materials obtained in each embodiment and comparative example were tested using a Fourier transform infrared spectrometer, and the obtained infrared absorption spectrum data are shown in Table 5 below.
[0165] Table 5 Comparison of infrared absorption spectra of examples and comparative examples
[0166]
[0167]
[0168] It can be seen from Table 5 that the positive electrode sheet without adding conductive carbon material (Comparative Example 7) and the positive electrode sheet without adding collage agent (Comparative Example 9) have the same conductivity as that of the positive electrode sheet at 1500 cm -1 ~2000cm -1 There is no obvious absorption peak at 1500cm, so there is no conjugated large π bond or cumulative double bond. The nickel-rich oxide with conductive carbon material collage (Examples 1, 2, 3, Comparative Examples 1, 2, 3, 4, 5, 6, 8, 10, 11, 12) has a peak at 1500cm -1 ~2000cm -1 Obvious absorption peaks are shown at all places, indicating the presence of large π bonds or cumulative double bonds; and the absorption peak of the spectrum is red-shifted. The formation of π bonds reduces the energy difference between energy levels, thereby reducing the electron transition energy, and then the absorption peak is red-shifted, indicating the existence of π-π conjugation effect. Therefore. It is explained that the positive electrode material and the conductive carbon material obtained by the collage method provided in the specific embodiment of the present application are not simply mixed, but orderly collage is achieved under the action of the collage agent, forming a specific interaction, making the composite of the conductive carbon material and the positive electrode material more controllable, thereby facilitating the design of a positive electrode sheet with an ultra-high active material ratio.
[0169] In addition, in the description of this application:
[0170] NMP: N-methylpyrrolidone, DMF: N,N-dimethylformamide,
[0171] D50: 50% passing particle size;
[0172] NCM: Lithium Nickel Cobalt Manganese Oxygen Ternary Layered Material (Li 1+m Ni x Co y Mn 1-x-y O2, x≥0.6, 0≤y≤0.4, 0≤m≤0.1);
[0173] NCA: Lithium Nickel Cobalt Aluminum Oxygen Ternary Layered Material (Li 1+m Ni x Co y Al 1-x-y O2, x≥0.6, 0≤y≤0.4, 0≤m≤0.1);
[0174] NCMA: Lithium nickel manganese cobalt aluminum oxygen ternary layered material (Li 1+m Ni x Co y Mn z Al 1-x-y-z O2, x≥0.6, 0≤y≤0.4, 0≤z≤0.4, 0≤m≤0.1).
[0175] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example.
[0176] Although the embodiments of the present application have been shown and described, those skilled in the art will appreciate that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present application, and that the scope of the present application is defined by the claims and their equivalents.
Claims
1. A positive electrode material, characterized in that: include: An amphiphilic surfactant, an adhesive, a nickel-rich oxide and a conductive carbon material, wherein the nickel-rich oxide and the conductive carbon material are spliced and matched by the amphiphilic surfactant; the mass percentage of the conductive carbon material in the positive electrode material is w1, wherein w1 satisfies: w1≤2wt%, and the conductive carbon material includes a zero-dimensional conductive carbon material, a one-dimensional conductive carbon material and a two-dimensional conductive carbon material; The matching relationship between the nickel-rich oxide and the conductive carbon material is related to the D50 of the nickel-rich oxide and the dimension of the conductive carbon material. α is defined as the ratio of the zero-dimensional conductive carbon material to the surface area of the nickel-rich oxide. The ratio of the two-dimensional conductive carbon material to the surface area of the nickel-rich oxide satisfies: 1-α; When the D50 satisfies: 0.9 μm ≤ D50 ≤ 3.0 μm, the α satisfies: 0.6 ≤ α ≤ 1.0; When the D50 satisfies: 3.0 μm<D50≤11 μm, the α satisfies: 0.3≤α≤0.7; When the D50 satisfies: when 11 μm<D50≤15 μm, the α satisfies: 0≤α≤0.4; Define t as the aspect ratio of the one-dimensional conductive carbon material; When the D50 satisfies: 0.9 μm ≤ D50 ≤ 3.0 μm, the t satisfies: t>700; When the D50 satisfies: 3.0 μm<D50≤11 μm, the t satisfies: 300≤t≤700; When the D50 satisfies: 11 μm<D50≤15 μm, the t satisfies: t≤300.
2. The positive electrode material according to claim 1, characterized in that The D50 of the nickel-rich oxide satisfies: 0.9 μm≤D50≤15 μm.
3. The positive electrode material according to claim 2, characterized in that The D50 of the nickel-rich oxide satisfies: 3.0 μm≤D50≤11 μm.
4. The positive electrode material according to claim 1, characterized in that Based on the amount of the nickel-rich oxide being 100 g, the amount of the zero-dimensional conductive carbon material corresponding to m is D0 In g, the thickness of the conductive carbon material is defined as δ, the compacted density of the nickel-rich oxide powder is defined as p, the conductivity of the conductive carbon material is defined as σ, the particle size of the conductive carbon material is defined as 2r, and the m D0 Satisfies the following formula (I): m D0 =4*π*((D50 / 2)+r) 2 *4 / 3*r*α*2.2 / σ(I); Corresponding to the amount of the two-dimensional conductive carbon material m D2 In g, the following formula (III) is satisfied: m D2 =4*π*(D50 / 2) 2 *(1-a)*δ*2.2 / σ (III); Corresponding to the amount m of the one-dimensional conductive carbon material D1 In g, the m D1 Satisfies the following formula (II): m D1 =100 / (p*(4 / 3)*π*(D50 / 2) 3 )*8*3D50*π*(3D50 / t)*2*2.2 / σ (II).
5. The positive electrode material according to claim 4, characterized in that When the D50 satisfies: 0.9 μm ≤ D50 ≤ 3.0 μm, The m D0 Meet: 0.5g≤m D0 ≤0.8g; m D1 Meet: 0.08g≤m D1 ≤0.3.g; m D2 Satisfy: 0.1≤m D2 ≤0.3g; When the D50 satisfies: 3.0 μm<D50≤11 μm, The m D0 Satisfy: 0.3 ≤ m D0 ≤0.7g; m D1 Meet: 0.08g≤m D1 ≤0.3.g; m D2 Satisfy: 0.2 ≤ m D2 ≤0.4g; When the D50 satisfies: When 11μm<D50≤15μm, The m D0 Satisfy: 0.2 ≤ m D1 ≤0.5g; m D1 Satisfy: 0.08 ≤ m D1 ≤0.3g; m D2 Satisfy: 0.3 ≤ m D2 ≤0.5g.
6. The positive electrode material according to claim 1, characterized in that The zero-dimensional conductive carbon material is selected from one or more spherical or point-shaped carbon materials; The one-dimensional conductive carbon material is selected from one or more linear or chain-shaped carbon materials; The two-dimensional conductive carbon material is selected from one or more of flaky or planar carbon materials.
7. The positive electrode material according to claim 1 or 6, characterized in that The zero-dimensional conductive carbon material is selected from one or more of conductive carbon black, fullerene, and carbon quantum dots; The one-dimensional conductive carbon material is selected from one or more of carbon nanotubes and carbon nanofibers; The two-dimensional conductive carbon material is selected from one or more of graphene and graphyne.
8. The positive electrode material according to claim 1, characterized in that The nickel-rich oxide is selected from one or more of a lithium nickel cobalt manganese oxygen ternary layered material, a lithium nickel cobalt aluminum oxygen ternary layered material and a lithium nickel manganese cobalt aluminum oxygen ternary layered material.
9. The positive electrode material according to claim 8, characterized in that The lithium nickel cobalt manganese oxygen ternary layered material has the following structure: Li 1+m Ni x Co y Mn 1-x-y O2, x≥0.6, 0≤y≤0.4, 0≤m≤0.1; the lithium nickel cobalt aluminum oxygen ternary layered material has the following structure: Li 1+m Ni x Co y Al 1-x-y O2, x≥0.6, 0≤y≤0.4, 0≤m≤0.1; the structure of the lithium nickel manganese cobalt aluminum oxygen ternary layered material is as follows: Li 1+m Ni x Co y Mn z Al 1-x-y-z O2, x≥0.6, 0≤y≤0.4, 0≤z≤0.4, 0≤m≤0.
1.
10. The positive electrode material according to claim 1, characterized in that The amphiphilic surfactant is selected from DSPE-MPEG, CH3(CH2) 11 SO4Na, [(C 16 H 33 )N(CH3)3]Br and PVP or more.
11. A positive electrode sheet for a lithium-ion battery, characterized in that: Comprising the positive electrode material according to any one of claims 1-10.
12. The method for preparing a lithium ion battery positive electrode sheet according to claim 11, characterized in that: The steps include: Step 1: adding an amphiphilic surfactant to a dispersion of a conductive carbon material; Step 2: After the dispersed system obtained in step 1 is evenly dispersed, nickel-rich oxide is added, stirred, and washed to obtain nickel-rich oxide powder with conductive carbon material collaged thereon; after the collage is completed, the powder is collected; Step 3: The nickel-rich oxide with the conductive carbon material obtained in step 2 is mixed with a binder and NMP and evenly coated on the aluminum foil; and the positive electrode sheet of the lithium-ion battery is obtained through drying and rolling.
13. The preparation method according to claim 12, characterized in that: The mass percentage of the surfactant added in the conductive carbon material dispersion in the step 1 is w2, wherein w2 satisfies: 0.01wt%≤w2≤0.2wt%.
14. The preparation method according to claim 13, characterized in that: The w2 is 0.04wt%.
15. A lithium ion battery, characterized in that: The lithium-ion battery comprises the lithium-ion battery positive electrode sheet according to claim 11 or the lithium-ion battery positive electrode sheet prepared by the preparation method according to any one of claims 12 to 14.
Citation Information
Patent Citations
Lithium ion battery
CN104362346A
Preparation method of lithium nickel cobalt manganate anodecathode composite material for lithium ion battery
CN108155358A